Conservation and Rehabilitation of Hussain Sagar Lake Andhra Pradesh - India - Sarvotham Rao, C. (Indian Forester, 2006)
This paper suggests the constitution of a single nodal agency called Hussain Sagar Development Authority (H.S.D.A.) for carrying out various Lake conservation and rehabilitation works. To save the Lake area from encroachment, a suggestion is made, to declare Hussain Sagar, a fresh water Lake, as a protected forest, under section 24 of A.P. Forest Act. with improved water quality of the lake, suggestion is made to declare it as a Bird Sanctuary under A.P. Wild Life (Protection) Act.